Evaluation of different extraction method for the isolation of cimetidine and ranitidine from human plasma for HPLC analysis - Helal Uddin, A.B.M.; Awang, Mohamed; Rahman, Md. Mokhlesur; Khan, Umeed Ali (2012)
Cimetidine and ranitidine are classified as the H2-receptor antagonists (H2 antagonist). These classes of drugs used to block the action of histamine on parietal cells in the stomach, decreasing the production of acid by these cells. H2 antagonists are widely used in the treatment of gastro oesophageal reflux, gastric and duodenal ulceration. Malaysian government has implemented bio equivalence requirements for manufacturing all generic drugs, cimetidine and ranitidine are also listed with other high demand generic drugs. The study focused on the preliminary chromatographic detection and determination of cimetidine and ranitidine in human plasma which eventually can be used for bioequivalence study of generic formulation of cimetidine and ranitidine. Different sample extraction process were evaluated namely protein precipitation, solvent extraction and solid phase extraction (SPE). It was found for both cimetidine (89%) and ranitidine (87%) showed a better recovery using SPE. With solvent extraction cimetidine showed comparable recovery (85%) using ethyl acetate as a solvent of choice and dichloromethane for ranitidine (82%). For the protein precipitation technique both cimetidine (75%) and ranitidine (73%) showed a lower recovery compared to the other method. HPLC method was used for the analysis of the spiked plasma samples. Chromatographic separation was obtained using a C18 column and mobile phase was a combination of phosphate buffer and acetonitrile. Elution of cimetidine and ranitidine were detected with a UV-Vis detector at 230 nm wavelength.